Misunderstanding about the Usuli Maxim "no Ijtihad in the presence of a text" and its clarifications - Amanullah, Muhammad (Zes Rokman Resources, 2016)
There is a misunderstanding among some students and scholars of Islamic jurisprudence that if a Qur’anic or Sunna’ic text is available on a particular issue, in order to derive the rule for this issue, neither is ijtihad required nor is it allowed. Rather, this text is sufficient to know the rule and implement it. This misunderstanding goes back to a wellknown usuli maxim: “No ijtihad in the presence of a text.” Using the method of critical analysis, this research intends to remove this misunderstanding and provide the correct understanding about this maxim and issues related to it.